Genome-Wide SNP Discovery and Mapping QTLs for Seed Iron and Zinc Concentrations in Chickpea (Cicer arietinum L.) - Sab, Syed; Lokesha, Ramappa; Mannur, D. M.; Somasekhar,; Jadhav, Kisan; Mallikarjuna, Bingi Pujari; C, Laxuman; Yeri, Sharanbasappa; Valluri, Vinod; Bajaj, Prasad; Chitikineni, Annapurna; Vemula, AnilKumar; et al. (Frontiers in Nutrition, 2020)
Biofortification through plant breeding is athe cost effective and sustainable approach towards addressing micronutrient malnutrition prevailing across the globe. Screening of cultivars for micronutrient content and , identification of QTLs/genes and markers help in the development of biofortified varieties in chickpea (Cicer arietinum L.). With thean aim of identifying the genomic regions controlling the seed-Fe and Zn concentrations, the F2:3 population derived from athe cross between MNK-1 and Annigeri 1 was genotyped using genotyping by sequencing approach and evaluated for seed-Fe and Zn concentration. An intra-specific genetic linkage map comprising 839 SNPs spanning a total map distance of 1088.04 cM with an average marker density of 1.30 cM, was constructed. By integrating the linkage map data with the phenotypic data of the F2:3 population, a total of 11 QTLs were detected for seed -Fe concentration on CaLG03, CaLG04 and CaLG05, with phenotypic variation explained ranginged from 7.2% (CaqFe3.4) to 13.4% (CaqFe4.2). For seed -Zn concentration, 8 QTLs were identified on CaLG04, CaLG05 and CaLG08. The QTLs individually explained phenotypic variations ranginged between 5.7% (CaqZn8.1) and 13.7% (CaqZn4.1). Three QTLs for seed -Fe and Zn concentrations (CaqFe4.4,CaqFe4.5 and CaqZn4.1) were co-located in the “QTL-hotspot” region, on CaLG04, that harbours several drought tolerance- related QTLs. We identified genes in the QTL regions that encode iron-sulphur metabolism and zinc dependent alcohol dehydrogenase activity on CaLG03, iron ion binding oxidoreductase on CaLG04, zinc- induced facilitator-like protein and ZIP zinc/iron transport family protein on CaLG05. These genomic regions and the associated markers associated can be used infor marker-assisted selection tofor increaseing seed-Fe and Zn concentrations in agronomically superior chickpea varieties.